Self-service technology in supermarkets – Do frontline staff still matter? - Sharma, Piyush; Ueno, Akiko; Kingshott, Russel (Elsevier, 2020)
This paper uses the concept of psychological distance under construal level theory to explore the differences in the customers’ evaluations of overall store quality, satisfaction and loyalty, based on their experiences with the traditional staff-checkout method and the relatively new selfcheckout machines. Two empirical studies, a field survey with retail shoppers in UK (N1=313) and an online survey with members of a consumer panel in Australia (N2=474), show that the perceived quality of staff-checkout has a stronger positive impact on the overall store quality, satisfaction and loyalty, than the quality of self-checkout. Similarly, satisfaction with staffcheckout has a stronger positive effect on store satisfaction and loyalty, than the satisfaction with self-checkout. Finally, loyalty to staff-checkout also has a stronger positive influence on store loyalty, than the loyalty towards self-checkout. These results show that despite growing use of self-service technology, frontline staff continue to be important for overall store evaluations.